Polemik Poligami Dalam Hukum Islam Dan Tinjauan Hak Asasi Manusia - Umi Salamah (DIMAR: Jurnal Pendidikan Islam, 2019)
Discussing polygamy always supports Islam which clearly allows polygamy on the basis of QS. An-Nisa> (3: 4), here the author tries to describe polygamy from a human rights perspective regardless of religious and social contexts. So as not to marginalize women in this context. It is clear that polygamy exists in Islam indirectly to elevate the status of women who are in an equal position with men. And polygamy was a form of executive in a special situation at that time, not an order to have more than one wife.